Pengaruh Terpaan Media Sosial @Beritasatu terhadap Minat Berdonasi - Hidayatullah, Muhamad Ivan; Safitri, Dini; Putri, K. Y. S.; Sutjipto, Vera Wijayanti; Prananingrum, Elisabeth Nugrahaeni; Sary, Marisa Puspita (Jurnal Common, 2023)
Aksi Cepat Tanggap or abbreviated as ACT is one of the largest philanthropic institutions in Indonesia. During ACT's development, Bareskrim Polri suspects that there was a misuse of aid funds made by ACT for the victims of the Lion Air JT-610 plane crash in 2018. These findings were conveyed by the police after the Financial Analysis and Transaction Reporting Center or PPATK stated that there was a myriad of financial problems at ACT. This study uses a quantitative approach, with data collection methods using questionnaires. The sampling technique for this study used a census technique so that the population, as well as the sample for this study, were 106 Instagram followers @beritasatu who liked the post entitled "Polri Investigate Allegations of Misappropriation of Funds at ACT" which was uploaded on July 9, 2022. The results of the analysis in this study indicate that exposure to Instagram social media @beritasatu has a positive and significant effect on the interest in donating Instagram followers @beritasatu to philanthropic institutions. The relationship between media exposure and intention to donate was also stated to be strong. Calculation of the value of the coefficient of determination or R2 produces several 0.942. This means that media exposure has an influence of 94.2 percent on the interest in donating. While the remaining 5.8 percent is the contribution of other variables besides media exposure.